Predominance of emm4 and antibiotic resistance of Streptococcus pyogenes in acute pharyngitis in a southern region of Korea. Issue 7 (6th June 2019) - Kim, Seungwook; Lee, Seungjun; Park, Hyunwoong; Kim, Sunjoo
Abstract : Background. Streptococcus pyogenes is the most common cause of bacterial pharyngitis. Genotyping of emm is useful for molecular epidemiological survey of S. pyogenes . Antibiotic resistance data are needed for empirical treatments. Methods. In total, 358 children in Changwon, Korea who had pharyngitis symptoms were subjected to throat cultures to isolate S. pyogenes in 2017. emm genotyping was performed by direct sequencing. An antibiotic susceptibility test was performed using the disk diffusion method for erythromycin (ERY), clindamycin (CLI), tetracycline (TET) and ofloxacin (OFX). Screening for macrolide resistance phenotype and its determinants was performed for the ERY-resistant strains. Results. A total of 190 strains (53.1 %) of S. pyogenes were isolated from 358 children. The most frequent emm genotype was emm 4 (53.2 %), followed by emm 89 (12.6 %), emm 28 (11.6 %) and emm 1 (10 %). Antibiotic resistance rates to ERY, CLI, TET and OFX were 3.2 %, 2.6 %, 1.1 % and 2.6%, respectively. There were five isolates of the cMLSB phenotype having the ermB gene and one M phenotype harbouring the mefA gene. Conclusions. The distribution of emm genotypes was quite different from those previously reported in Korea. emm 4 accounted for more than 50 % of the genotypes. Macrolide resistance rates remained very low, but five of six ERY-resistant strains displayed the cMLSB phenotype.